Examining the Effectiveness of a Pilot Physical Literacy–Based Intervention Targeting First-Year University Students: The PLUS Program. (May 2019) - Kwan, Matthew Y. W.; Graham, Jeffrey D.; Bedard, Chloe; Bremer, Emily; Healey, Cierra; Cairney, John
The transition into university is often considered the first major life transition and is associated with significant declines in physical activity (PA). It remains, however, unclear how to best prevent or attenuate these declines. The concept of physical literacy (PL) and the enhancement of PL may hold some promise, as it is considered foundational for lifelong PA engagement. Specifically, it targets the motivation, confidence, physical competence, knowledge, and understanding to maintain PA. The purpose of this study was to evaluate the effectiveness of a pilot PL-based intervention. First-year university students ( N = 65, M age = 17.85 ± 0.51; n = 46 females) were enrolled in a quasi-experimental study. Participants in the intervention condition ( n = 26) entered a 12-week program intentionally designed to facilitate novel movement skills through aerial, water, and land-based activities, within a fun and engaging group-based environment. Participants in the control condition completed baseline and follow-up assessments only. All participants completed baseline and follow-up assessments of movement competence, motivation, knowledge, and confidence. Results found a significant time by condition interaction, F (1, 58) 4.92, p = .03, η p 2 = 0.08 in PL, suggesting the intervention was effective in enhancing overall PL. There were also significant time by condition interactions for motivation, F (1, 59) 5.19, p = .03, η p 2 = 0.08, and knowledge and understanding, F (1, 59) 6.90, p = .01, η p 2 = 0.11 when examining PL subdomains. Overall, results from our pilot PL-based intervention show promise as a modality to help first-year university students maintain active lifestyles, but future trials with larger samples are required.